Temporal variability of meteorological and oceanographic parameters in Tuban Waters, Indonesia, and their relationships with ENSO and IOD - Anggilia, Elsa; Ma’arif, Rodhi Naufal; Sawiji, Asri; Santoso, Eko Hadi (Journal of Marine Resources and Coastal Management, 2026)
Global climate variability influences meteorological and oceanographic conditions in Indonesian coastal waters, including Tuban Waters. This study aimed to analyze the temporal variability and anomalies of meteorological and oceanographic parameters and to evaluate the relationships between the El Niño–Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) with environmental variability in Tuban Waters during 2015–2024. Meteorological and oceanographic data were obtained from BMKG, NOAA, and NASA Ocean Color, including rainfall, sea surface temperature (SST), chlorophyll-a concentration, wind speed, wave height, current velocity, tidal elevation, the Oceanic Niño Index (ONI), and the Dipole Mode Index (DMI). Trend analysis, anomaly analysis, and Spearman correlation analysis were applied to assess temporal variability and climate–environment relationships. The results showed decreasing trends in wind speed, wave height, and rainfall, whereas current velocity exhibited moderate variability without a clear long-term trend. Rainfall variability was significantly negatively correlated with both DMI (ρ = −0.353, p < 0.01) and ONI (ρ = −0.293, p < 0.01), indicating that positive IOD and El Niño conditions were generally associated with reduced rainfall. SST anomalies were significantly negatively correlated with DMI (ρ = −0.332, p < 0.01), whereas their relationship with ONI was weak and not statistically significant. Chlorophyll-a anomalies exhibited weak correlations with both climate indices, suggesting that local oceanographic processes, particularly nutrient dynamics and water-column mixing, played a greater role in regulating biological variability. Overall, the results indicate that rainfall variability in Tuban Waters is influenced by both ENSO and IOD, whereas SST variability is more closely associated with IOD and regional oceanographic processes. In contrast, chlorophyll-a variability is primarily controlled by local oceanographic conditions, with only limited influence from large-scale climate variability. These findings provide an integrated understanding of meteorological and oceanographic variability and their interactions with climate variability in Tuban Waters, supporting coastal environmental monitoring and management.